KEBIJAKAN PENANGANAN PEMBIAYAAN MUḌĀRABAH BERMASALAH PADA KOPWAN BMT AN-NISA’ YOGYAKARTA - Kamal, Mustafa (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Islam Indragiri, 2016)
This research analyzed the policy of KopWan BMT An Nisa’ Yogyakartato handle the muḍārabaḥ problem. This research is including into descriptive qualitative research. The data contain of the primary and secondary data which is caused the financing problem and the handling of muḍārabah finance in KopWan BMT An Nisa’ and todetermineits effectiveness. The data analysis used is qualitative analysis. Based on the result of research, it was recognized that the factor which caused the problems in the costing of muḍārabah are incorrect cost analysis, dishonesty of the costumers, uncommitted of the costumers, the bankruptcy of the costumers, and the costumers characteristics. The way to solve the problems by giving the suspension firtsly and than Rescheduling, Restructuring, and Reconditioning and proveditworked well